Analisis Kualitas Pelayanan Nanostore Pada Masa Pandemi Covid-19 - Purnama, Tiana Chandra (Asosiasi Ahli Administrasi Indonesia, 2021)
This study aims to determine how the quality of nanostore services provided to customers and to determine the highest and lowest dimensions of service quality during the Covid-19 period in Sumedang Regency. The research method used is descriptive analysis with a quantitative approach where the results of the analysis are the calculation of the mean, standard deviation, maximum value and minimum value. Data collection was carried out by distributing questionnaires to 120 respondents. The results of the study stated that the quality of services provided by nanostores to customers during the Covid-19 period in Sumedang Regency was in the good category. The dimension that has the highest value is the emphaty dimension, while the one with the lowest value is the tangibles dimension. From each dimension, there are indicators that need to be improved, namely the appearance of the officers, the use of tools, and the ability of the officers to use tools.